2020
DOI: 10.3389/fvets.2020.00333
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oyster Mushroom Waste on Growth Performance, Immunity and Intestinal Morphology Compared With Antibiotics in Broiler Chickens

Abstract: Oyster mushroom waste (OMW) is a by-product of the agriculture industry with valuable antimicrobial, antioxidant, antifungal, and prebiotic properties. This by-product might be a useful alternative to antibiotic growth stimulators in poultry nutrition. The purpose of this research was to test the impact of OMW on the immune responses and on the morphology of intestine of broiler chickens. Four dietary therapies with five replicas of 15 birds in each, totalling 300 day-Ross 308 broiler chickens, were utilized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 78 publications
(99 reference statements)
7
4
1
Order By: Relevance
“…Inclusion of dried mushroom in diets has been reported to increase synthesis of superoxide dismutase (SOD), catalase, glutathione, glutathione reductase, glutathione peroxidase (GSH-Px) and glutathione S-transferase production in meat (Giannenas et al 2010, Mahfuz et al 2020b, Mahfuz et al 2020a, thereby affirming the increased enzyme activity in the present study. GSH-Px activity has been discovered to decreased after antibiotics treatment, therefore the positive effect exhibited by Pleurotus ostreatus affirms reports of studies of its strong evidence of antioxidant activity in vitro (Hassan et al 2020). Thiobarbituric Acid Reactive substances was highest at 2000 mg/l but least in meat obtained from the control group and 4000 mg/l.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Inclusion of dried mushroom in diets has been reported to increase synthesis of superoxide dismutase (SOD), catalase, glutathione, glutathione reductase, glutathione peroxidase (GSH-Px) and glutathione S-transferase production in meat (Giannenas et al 2010, Mahfuz et al 2020b, Mahfuz et al 2020a, thereby affirming the increased enzyme activity in the present study. GSH-Px activity has been discovered to decreased after antibiotics treatment, therefore the positive effect exhibited by Pleurotus ostreatus affirms reports of studies of its strong evidence of antioxidant activity in vitro (Hassan et al 2020). Thiobarbituric Acid Reactive substances was highest at 2000 mg/l but least in meat obtained from the control group and 4000 mg/l.…”
Section: Resultssupporting
confidence: 83%
“…The increased serum albumin content observed at day 56 may be related to direct effect of the antioxidant compounds such as phenols, ascorbic acid, vitamin E and β-carotene (Yang et al 2002, Ekunseitan et al 2017) contained in Pleurotus ostreatus capable of positively influencing the immune status of the birds, cellular response, maintenance of oncotic pressure and balance (Melilo 2013, de Lima et al 2020. This outcome of the current study contradicts Hassan et al (2020) who observed no effect dietary supplementation of oyster mushroom blood total protein, total albumin, globulin, or urea nitrogen concentrations between the treatment groups and control.…”
Section: Resultscontrasting
confidence: 65%
“…affect lymphoid organ weights(Attia & Al-Harthi, 2015;Hassan et al, 2020;Mahfuz et al, 2018;Shamsi et al, 2015).Natural antioxidants maintain the health of animals and humans by regulating immune routes that adjust and improve the detrimental traces of inordinate generation of reactive oxygen species(Puertollano et al, 2011). In the current trial, the NDV titre increased withTA B L E 2Abbreviations: DWG, daily weight gain; DFI, daily feed intake; FCR, Feed conversion ratio; GP, garlic powder; MP, mushroom powder; SEM, standard error of means.TA B L E 3…”
mentioning
confidence: 99%
“…In addition, because of the traditional recognition of low-energy, high-fibre feed ingredients in animal feed, animal breeder are usually rarely willing to increase the fibre content of animal diets (Buxton and Redfearn 1997). However, previous studies have repeatedly shown that the addition of high fibre is beneficial to animal health (Desai et al 2016;Teng et al 2017;Hassan et al 2020). In addition to increasing the strength of the animal's intestinal barrier, high fibre also has a relief effect on the animal's inflammatory response (Zou et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, the inevitable by-products of crop production are often not effectively used. Common agricultural by-products include wheat bran, bean hull, rice bran, straw, and corn stalks, olive cake and prosopis pod (El-Ghamry et al 2005;Eshel et al 2014;Jones et al 2019;Al-Harthi et al 2019aHassan et al 2020). At present, many agricultural by-products have been incinerated, buried or used as adjusting materials for poultry and livestock compost.…”
Section: Introductionmentioning
confidence: 99%